1994
DOI: 10.1037/0022-0167.41.3.296
|View full text |Cite
|
Sign up to set email alerts
|

Components of the psychotherapy relationship: Their interaction and unfolding during treatment.

Abstract: 1985) suggested that all counseling and psychotherapy relationships, regardless of theoretical orientation, consist of three components: a working alliance, a transference configuration (including therapist countertransference), and a real relationship. Drawing on theoretical and research literature and using clinical examples, this article offers 19 propositions about how these three relationship components interact with one another, how each operates across the course of psychotherapy, and how they affect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
338
1
5

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 360 publications
(360 citation statements)
references
References 22 publications
16
338
1
5
Order By: Relevance
“…The importance of the therapy relationship in the therapy encounter is virtually undisputed (Gelso & Carter, 1994). Akin to the corollary to Proposition 3 about the differential influence of the content and process of a therapy interaction on therapist learning, the quality and unfolding of the therapy relationship (particularly in terms of working alliance and real relationship, as described by Gelso & Carter, 1985;1994) likely influences the content and amount that therapists learn from clients.…”
Section: Corollary 2a: While Overlap Is Likely the Construct Of Learmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the therapy relationship in the therapy encounter is virtually undisputed (Gelso & Carter, 1994). Akin to the corollary to Proposition 3 about the differential influence of the content and process of a therapy interaction on therapist learning, the quality and unfolding of the therapy relationship (particularly in terms of working alliance and real relationship, as described by Gelso & Carter, 1985;1994) likely influences the content and amount that therapists learn from clients.…”
Section: Corollary 2a: While Overlap Is Likely the Construct Of Learmentioning
confidence: 99%
“…Given the role of therapist, client, and therapy relationship characteristics on therapy process and outcome (e.g., Beutler et al, 2004;Clarkin & Levy, 2004;Gelso & Carter, 1994), it is not surprising that all participants also reported that they influence the amount one learns from a client.…”
Section: Variables That Contribute To Learning More From Clientsmentioning
confidence: 99%
“…It is well established that the therapeutic alliance is critical to successful counselling (Gelso and Carter, 1994;Wampold, 2000). Horvath and Luborsky (1993) identify openness, respect and a collaborative bond as essential components of the therapeutic alliance.…”
Section: Client Satisfaction Surveymentioning
confidence: 99%
“…On the one hand, countertransference may cause therapists to act defensively in accordance with their own needs, perceive clients in distorted fashion, and exhibit poor clinical judgment. On the other hand, the insight that may be gleaned from countertransference can deepen therapists' awareness of relationship dynamics and provide valuable information about the course of treatment (Gelso & Carter, 1994;Gorkin, 1987;Singer & Luborsky, 1977;Tauber, 1954). Freud (1910Freud ( /1959 first introduced the term countertransference to refer to the analyst's unconscious and defensive reactions to the patient's transference.…”
mentioning
confidence: 99%